Effectiveness of Reality Therapy–Based Couple Therapy and Emotion-Focused Couple Therapy on Irrational Beliefs in Betrayed Couples - Akbari , Fahimeh; Azmoodeh, Masoumeh; Hoseini Nasab , Seyed Davoud (Mental Health and Lifestyle Journal, 2026)
The present study was conducted to determine the difference in the effectiveness of couple therapy based on reality therapy and emotion-focused couple therapy on irrational beliefs in betrayed couples across three phases: pretest, posttest, and follow-up. This study was applied in nature and employed a quasi-experimental design using a pretest–posttest structure with a control group. The statistical population consisted of all couples who had experienced marital infidelity and sought services from counseling centers in the city of Sari in 2023. From this population, 64 individuals were selected through convenience sampling based on inclusion and exclusion criteria and were randomly assigned to two experimental groups and one control group (22 participants in the reality therapy–based couple therapy group, 22 in the emotion-focused couple therapy group, and 20 in the control group). Data were collected using the Jones Irrational Beliefs Questionnaire (1969) at the pretest, posttest, and follow-up stages. In the posttest phase, one couple from the reality therapy group withdrew from the study, and in the follow-up phase, one couple from the emotion-focused therapy group also withdrew; therefore, data from 60 participants were analyzed. Data analysis was performed using repeated-measures ANOVA in SPSS-20. The findings indicated a significant difference between the effectiveness of reality therapy–based couple therapy and emotion-focused couple therapy on irrational beliefs in betrayed couples across the three stages. Specifically, both therapeutic approaches were effective compared to the control group; however, reality therapy–based couple therapy had the greatest impact in reducing irrational beliefs. Furthermore, significant changes from pretest to posttest reflected the effectiveness of the interventions, and changes from posttest to follow-up indicated relative stability of outcomes, particularly in emotion-focused couple therapy.